A Novel Strategy to Synthesize Dual Blue Fluorescent‐Magnetic EuCl2 Nanocrystals via One‐Pot Method with Controlled Morphologies Using Urea. (18th July 2018) - Zhao, Tianxin; Xin, Jingwei; Jiang, Yingnan; Zhao, Yue; Zhao, Yueqi; Zhao, Yu; Sun, Weiyi; Yang, Bai; Lin, Quan
Abstract: Divalent state europium nanocrystals (Eu II NCs) have tremendous number of applications such as biological detection, solar cells, medical imaging, and so on. Here, a ready synthetic one‐pot approach to prepare dual blue fluorescent‐magnetic EuCl2 NCs is reported. EuCl3 is reduced by the reducing agent urea, while the oleic acid and oleyl amine are used as the capping ligand. A serial of analysis, such as X‐ray photoelectron spectroscopy, electron spin resonance, and zero‐field cooling magnetization curve/field cooling magnetization curve are performed to confirm the successful reduction of EuCl2 . It is novel that the morphology and size of produced EuCl2 NCs could be adjusted efficiently by the reducing agent urea, including rod shaped, wire shaped, and fiber shaped. The mechanism of controlling the size and morphology of synthetic EuCl2 NCs by the urea content is discussed in detail. What is more, it has been demonstrated that in this one‐pot method the homogeneous and complete nucleation needs to perform slowly in high temperature reaction stage, and then the uniformed crystals are gradually formed during the slow cooling process. That is an appealing strategy for tunable design and synthesis of multifunctional Eu II NCs. Abstract : The one‐pot method to fabricate multifunctional EuCl2 nanocrystals (NCs) is sketched in Scheme 1. The reactive system of EuCl3 and agent urea is set at 260 °C for 3 h, with oleyl amine and oleic acid as the capping ligands. After slowly cooling to room temperature, the prepared (divalent state) EuCl2 NCs exhibit good blue luminescent and paramagnetic properties.